2017
DOI: 10.1002/icd.2075
|View full text |Cite
|
Sign up to set email alerts
|

Emotion awareness and somatic complaints in preadolescence: The mediating role of coping strategies

Abstract: Somatic complaints are frequent among preadolescents with impaired emotion awareness and maladaptive coping strategies. In addition, coping strategies in response to stressful events have been suggested to affect the association between emotion awareness and somatic complaints. However, empirical support for this assumption is missing. In this study, we examined the extent to which emotion awareness and coping contributed uniquely to somatic complaints and the indirect effect of emotion awareness on somatic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
2
4
0
1
Order By: Relevance
“…Regarding the individual factors that might foster the development of somatic complaints, studies have highly emphasized the role of alexithymia (and its related construct of emotion awareness) as one of the most significant predictors of such conditions in adult populations [26]. Similar results have been found in studies with children and adolescents (e.g., [27,28]), and a recent systematic review [29] revealed that seven out of the eight studies comparing children with medically unexplained symptoms and healthy controls found that the former had higher levels of self-reported alexithymia.…”
Section: The Role Of Alexithymiasupporting
confidence: 56%
See 1 more Smart Citation
“…Regarding the individual factors that might foster the development of somatic complaints, studies have highly emphasized the role of alexithymia (and its related construct of emotion awareness) as one of the most significant predictors of such conditions in adult populations [26]. Similar results have been found in studies with children and adolescents (e.g., [27,28]), and a recent systematic review [29] revealed that seven out of the eight studies comparing children with medically unexplained symptoms and healthy controls found that the former had higher levels of self-reported alexithymia.…”
Section: The Role Of Alexithymiasupporting
confidence: 56%
“…Due to the inability to mentalize the bodily sensations associated with affective arousal and to analyze the situation from an external point of view, adolescents are not able to use their emotions to understand themselves and the cause of their pain. This would eventually lead to a greater focus on the signs of emotional arousal (e.g., fast heartbeat), eliciting further anxiety and overwhelming distress, which is more likely to be misinterpreted as sickness and an index of body malfunction [27,33]. Lumley et al [34] explained that alexithymia might lead to somatic complaints because it gives rise to undifferentiated arousal, which produces somatic sensations; these sensations, in turn, are amplified by alexithymic individuals who attribute them to illness-related causes rather than to psychological ones.…”
Section: The Role Of Alexithymiamentioning
confidence: 99%
“…More specifically, we predicted that a high level of somatic symptoms would mediate the link between previous experiences of victimization and emotion regulation. Focusing on one’s own physical symptoms makes individuals worry, anxious, concentrated on themselves, and unable to employ effective coping strategies, which can further increase their distress and make them incapable of relaxing and regulating arousal (Mazzone & Camodeca, 2018; Meerum Terwogt et al, 2006). For bullies, we expected that sensation seeking would mediate the relationship between bullying and emotion regulation, because the need for strong sensations and excitement activates individuals to continuously intensify the behavior in which they are involved in order to increase the thrill.…”
Section: The Present Studymentioning
confidence: 99%
“…Alongside the significant body of research on EA and ER skills in adolescents, only few studies have examined them in tandem, despite the strong association between them [ 30 ]. Among the studies which tested the contributions of both emotion awareness and regulation to mental health development composites scores were used, which either unified EA with ER [ 31 , 32 ], or measured overall levels of EA and ER with no distinction between specific EA/ER skills [ 20 , 33 ]. Therefore, more research is needed on the contribution of EA and ER to mental health while controlling for the effect of each other, and while disentangling to specific awareness and regulation strategies.…”
Section: Introductionmentioning
confidence: 99%